2006
DOI: 10.1177/0170840606068255
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Firm in its Market and Organizational Environment: Methodologies for Studying Corporate Social Responsibility

Abstract: The study of corporate social responsibility (CSR) can best be mainstreamed within the wider social science literature if it is defined as firms voluntarily assuming responsibility for their externalities, thereby setting the puzzle of how this can be reconciled with the maximization of shareholder value as the central challenge of the subject. Means of resolving the puzzle require modelling the firm interacting with its environment as both a market actor and as an organization, and in particular through the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(142 citation statements)
references
References 42 publications
1
128
0
12
Order By: Relevance
“…Implementing CSP is costly because, from an economic perspective, high CSP reflects a firm voluntarily internalizing its externalities (Lyon & Maxwell, 2008). Externalities, defined as the results of market transactions that are not themselves embodied in such transactions (Coase, 1960;Crouch, 2006), are typically not fully reflected in prices and so lead to a divergence of private and social costs (Dahlman, 1979;Pigou, 1962). In other words, CSP refers to nonmarket actions by which firms take "ownership of the externalities they generate" (Crouch, 2006(Crouch, , p. 1534.…”
Section: The Predominance Of Firm-level Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing CSP is costly because, from an economic perspective, high CSP reflects a firm voluntarily internalizing its externalities (Lyon & Maxwell, 2008). Externalities, defined as the results of market transactions that are not themselves embodied in such transactions (Coase, 1960;Crouch, 2006), are typically not fully reflected in prices and so lead to a divergence of private and social costs (Dahlman, 1979;Pigou, 1962). In other words, CSP refers to nonmarket actions by which firms take "ownership of the externalities they generate" (Crouch, 2006(Crouch, , p. 1534.…”
Section: The Predominance Of Firm-level Factorsmentioning
confidence: 99%
“…Externalities, defined as the results of market transactions that are not themselves embodied in such transactions (Coase, 1960;Crouch, 2006), are typically not fully reflected in prices and so lead to a divergence of private and social costs (Dahlman, 1979;Pigou, 1962). In other words, CSP refers to nonmarket actions by which firms take "ownership of the externalities they generate" (Crouch, 2006(Crouch, , p. 1534. In addition to the direct costs associated with CSP (see also Orlitzky, 2013), companies that are committed to CSP also incur transaction costs (Macher & Richman, 2008), which apply not only to social/environmental partnerships, but also to the adoption of any CSP initiative more broadly (King, 2007).…”
Section: The Predominance Of Firm-level Factorsmentioning
confidence: 99%
“…CSR is therefore corporations' way to construct and control consumers' behaviour and market. Creation of taste for environment protection and sustainability is one way of shaping customers' demand (market) for their products (Crouch 2006;Lombardo 2011).…”
Section: The Concept Of Corporate Social Responsibilitymentioning
confidence: 99%
“…CSR is therefore corporations' way to construct and control consumers' behaviour and market. Creation of taste for environment protection and sustainability is one way of shaping customers' demand (market) for their products (Crouch 2006;Lombardo 2011).Association of Tanzania Employers -ATE (2012), which is tripartite forum comprising of ATE on one side and government and trade unions on the other, confirmed that CSR has many advantages to the local community. It can offer financial contributions, it can also make some of the business's product or services available free or at low cost to charities and community groups.…”
mentioning
confidence: 99%
“…An emergent neoinstitutionalist literature directly tackles this problem (Crouch 2006;Doh and Guay 2006).For RT, perhaps even more critically, there is the risk of neglecting the rather obvious point that the capacity to deliver on the objectives of regulatory regimes (whether these are set within firms themselves or externally), within a system of business regulation, lies largely with those firms (Parker 2002).…”
Section: Differentiating Regulation and Csr Researchmentioning
confidence: 99%